Pengaruh Biaya Operasional dan Pendapatan Operasional, Net Operating Margin, Dana Pihak Ketiga dan Capital Adequacy Ratio terhadap Profitabilitas Bank Syariah - Rahma Aulia; Saiful Anwar (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2021)
Purpose: This study examined the effect of Operational Efficiency Ratio (BOPO), Net Operating Margin (NOM), Third Party Funds (DPK) and Capital Adequacy Ratio (CAR) On Profitability With Financing To Deposito Ratio (FDR) As Intervening Variable in Islamic Commercial Bank. Research Methodology: The sample used in this study was 11 banks with the sampling technique using purposive sampling. The analytical method used was multiple linear regression Results: The results show that the variables BOPO and NOM have no effect on FDR. DPK and CAR have a positive and significant effect on FDR. FDR and NOM have a positive and significant effect on Profitability. BOPO, DPK and CAR have no effect on Profitability. FDR is able to be an intervening variable in the relationship between DPK and CAR to Profitability. FDR is not able to be an intervening variable in the relationship between BOPO and NOM to Profitability. Limitations: The sample of this study was only 11 Islamic commercial banks and only used the Islamic banking sector in Indonesia, which is listed on the Indonesia stock exchange. Contribution: The research is helpful for further investigation. One of the guidelines in choosing which variables to use and which one to use in the study should be understood in selecting Islamic financial performance. Keywords: BOPO, NOM, DPK, CAR, Profitability, FDR